Unpacking pedagogy : new perspectives for mathematics classrooms - Walshaw, Margaret (International perspectives on mathematics education,, 2010)
This volume represents a serious attempt to understand what it is that structures the pedagogical experience. In that attempt there are two main objectives. One is a theoretical interest that involves examining the issue of the subjectivity of the teacher and exploring how intersubjective negotiations shape the production of classroom practice. A second objective is to apply these understandings to the production of mathematical knowledge and to the construction of identities in actual mathematics classrooms. To that end book contains substantial essays that draw on postmodern philosophies of the social to explore theory's relationship with the practice of mathematics pedagogy.Unpacking Pedagogy takes new ideas seriously and engages readers in theory development. Groundbreaking in content, the book investigates how our thinking about classroom practice in general, and mathematics teaching (and learning), in particular, might be transformed. As a key resource for interrogating and understanding classroom life, the book's sophisticated analyses allow readers to build new knowledge about mathematics pedagogy. In turn, that new knowledge will provide them with the tools to engage more actively in educational criticism and to play a role in educational change.